Work Culture Analysis, Professionalism, Work Motivation In Improving The Quality Of Employment Education In Padang State University - Adelyn Alista Utami; Aldri Frinaldi (Program Pascasarjana Universitas Negeri Makassar, 2020)
The big challenge facing bureaucracy is how they are able to carry out activities efficiently and effectively. Therefore, so far bureaucracy has been identified with convoluted performance, structure that is too large, full of collusion, corruption and nepotism, and there are no definite standards. Padang State University has currently carried out bureaucratic reform agendas from 2010 to 2014. Although not yet comprehensive and very well organized, the change agenda has been implemented and the results have been felt by employees and related stakeholders. However, the long road to bureaucratic reform continues, the challenges and problems of the bureaucracy have not been completely completed, requiring solutions and solutions to solve bureaucratic problems and create a professional bureaucracy. This study aims to determine the direct and indirect effects of work culture, professionalism and work motivation variables on the quality of work of educational staff at Padang State University. The method used is a quantitative method, with a survey approach. The study population was all education staff employees in the rector of Padang State University. The number of research samples was determined using the Slovin formula. The number of research samples as many as 160 people were determined by proportional stratified random sampling technique. The instrument used was a questionnaire that had been tested for validity and reliability. This study found that partially and simultan, work culture variables, professionalism and work motivation had a direct and indirect influence on the quality of work of educational staff at Padang State University.